Stability Control of Slopes in Open-Pit Mines and Resilience Methods for Disaster Prevention in Urban Areas: A Case Study of Fushun West Open Pit Mine - Jiaxing, Zhou; Fei, Li; Jin-an, Wang; Anqi, Gao; Chengyuan, He (Frontiers in Earth Science, 2022)
During the century-long mining process of the Fushun west open pit, slope slippage and deformation caused varying degrees of horizontal deformation, uneven settlement, and ground cracks on the surface of the urban areas, which caused a certain degree of damage to buildings and infrastructure and affected the livings of residents in the surrounding communities. In this study, a set of building reinforcement and community resilience enhancement methods that can resist slope deformation was proposed to improve the ability of urban areas to cope with slope geological hazards and emergency response. The main research contents included: Firstly, this paper systematically analyzed the deformation mechanism of the dip sloping and the inverse dip sloping section of the open pit mine, which was based on the field measured data and simulation calculation results. In other words, the horizontal deformation of the stratum in the dip sloping section was dominant, while the stratum in the inverse dip sloping section was prone to ground cracks and uneven settlement. In view of this, three surface deformation characteristic subdivisions of the surrounding urban area were proposed. In addition, a study on the damage characteristics of buildings with different types of foundations and structures under the influence of side slope deformation were carried out, and the anti-deformation reinforcement measures for load-bearing members mainly based on steel fiber concrete, carbon fiber materials and profile steel were proposed. Finally, a three-level disaster emergency setting system for urban areas around open pit mine was established, and the disaster prevention and resilience enhancement strategy for build and unbuilt the communities around the side slopes was constructed. The study aims to provide technical support to the overall resilience and response of the urban communities adjacent to open-pit mine slopes against consequent geological hazards and emergencies, thereby promoting sustainable urban development.